Constitutional Law and Social Change: A Global Perspective - Suratno, Ujang (Journal of Law and Social Politics, 2025)
Background: Constitutional law plays a fundamental role in shaping social change by influencing governance structures, human rights protection, and democratic resilience across diverse political and cultural contexts. As societies continue to evolve, constitutional frameworks are increasingly challenged by phenomena such as populism, digital transformation, global health crises, and climate change, requiring adaptive legal responses. Objective: This study aims to examine the dynamic relationship between constitutional law and social change from a global perspective, with a particular focus on how constitutional frameworks respond to and shape societal transformations through amendments, judicial interpretations, and landmark constitutional decisions. Methods: The research employs a qualitative approach by synthesizing doctrinal legal analysis, comparative constitutional studies, and selected global case studies. Relevant constitutional texts, judicial rulings, and scholarly literature are analyzed to identify patterns of constitutional adaptation across different legal systems. Results: The findings demonstrate that constitutional law functions both as a catalyst for progressive social change and as a stabilizing mechanism within political systems. While some jurisdictions utilize constitutional mechanisms to strengthen democracy and advance human rights, others experience constitutional regression through legalistic autocracy. Judicial independence, civic engagement, and the influence of international legal norms emerge as critical factors in sustaining constitutional resilience. Conclusion: This study concludes that constitutional law is an evolving legal instrument that both reflects and shapes social change. By highlighting global patterns of constitutional adaptation, the research contributes to contemporary constitutional discourse and provides insights for policymakers, legal scholars, and human rights advocates in fostering democratic resilience through responsive and principled legal frameworks.